2016
DOI: 10.12659/msm.897122
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rs2071410 on Furin with Transient Ischemic Attack Susceptibility and Prognosis in a Chinese Population

Abstract: BackgroundBecause genotype CG/GG of Furin rs2071410 can increase susceptibility to hypertension, this study investigated whether Furin rs2071410 is correlated with transient ischemic attack (TIA) susceptibility and prognosis.Material/MethodsThe odds ratios (ORs) and their 95% confidence intervals (95% CIs) were evaluated to assess the association of rs2071410 with TIA risk, and logistic regression was used to estimate the effects of various risk factors (e.g., diabetes, hypertension, and hyperlipidemia) on TIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…An elevated expression of furin in adipose tissue from obese mice compared with the lean controls found by an animal study14 further support this hypothesis. Moreover, the FURIN gene polymorphisms have been associated with abdominal obesity15 and associated metabolic disorders, for example, metabolic syndrome (MetS),16 hypertension,17 coronary artery disease18–20 and stroke21 in populations.…”
Section: Introductionmentioning
confidence: 99%
“…An elevated expression of furin in adipose tissue from obese mice compared with the lean controls found by an animal study14 further support this hypothesis. Moreover, the FURIN gene polymorphisms have been associated with abdominal obesity15 and associated metabolic disorders, for example, metabolic syndrome (MetS),16 hypertension,17 coronary artery disease18–20 and stroke21 in populations.…”
Section: Introductionmentioning
confidence: 99%
“…The NP family includes 3 well-characterized hormones—atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP), C-type natriuretic peptide (CNP), 16 and the related protease convertases (furin and corin). 17,18 Sequence variants in their coding genes, e.g., NPPA (the gene coding ANP), 19,20 NPPB (the gene coding BNP), 21 CORIN (the gene coding corin), 22,23 and FURIN (the gene coding furin) 24,25 but not NPPC (the gene coding CNP), have previously been related to susceptibility to IS and its main risk factors, e.g., hypertension and atherosclerosis. Although these studies highlight the contributions of genetic variants in the NP system to the risks of IS, additional underlying molecular mechanisms remain to be elucidated.…”
mentioning
confidence: 99%
“…130 A genetic study reported that the CG/ GG genotypes of the FURIN rs2071410 SNP are associated with ∼50% increased risk of transient ischemic attack (TIA), compared with the homozygous CC genotype (Table 2). 95 This SNP potentially contributes to a reduction in furin activity and an increase in hypertension, 35 a strong associated risk factor of TIA. 131 In stroke, however, GWAS meta-analyses have revealed that FURIN is one of the putative causal genes.…”
Section: ■ Ischemic Strokementioning
confidence: 99%